Analysis of the Financial Literacy Level of Generation Z College Students and Its Implications for the Use of Paylater in the Context of Economic Education - Suyono, Aji Prasetyo; Chandra, Yulian Ade; Mukhsin, Muhammad (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Describes the extent to which Gen Z students understand financial literacy and how it is applied to the use of PayLater. Methodology: This study uses a qualitative descriptive approach by providing questionnaires to Gen Z students in the cities of Surabaya, Semarang, Malang, Lumajang, and Jember in April 2025. Main Findings: The results show that the literacy level of Gen Z students is in the medium category. Then, the implication of this literacy level is that many respondents think that the use of paylater tends to influence shopping habits and can also influence lifestyle. Apart from that, regarding perceptions of paylater services as a whole, most respondents tend to choose neutral perceptions rather than positive or negative perceptions. Thus, there needs to be education through formal education, public campaigns, and easy access to financial information for students so that there is a balance between thinking ability and action in terms of financial management. Novelty/Originality of this study: This study develops and expands the theory of financial literacy with Gen Z students as the object of research.